Novel pyrazole-centered derivatives having mono/di chiral centered group as organocatalyst for henry reaction - Çetin, Adnan; Bildirici, İshak; Gümüş, Selçuk (Macedonian Journal of Chemistry and Chemical Engineering, 2020)
The chiral substituted pyrazole-3-carboxamides (4a-c), pyrazole-3-carboxylates (5a-c), pyrazole-3-thioureides (7a-c) and pyrazole-3,4-dicarboxamides (10a-c) were prepared via the pyrazolo-3-chlorocarbonyl 2, pyrazolo-3,4-dicarboxy methyl ester 3 with pyrazole-3-isothiocyanate 6 with different (R)-chiral amino al-cohols. All of the synthesized chiral compounds binding a pyrazole skeleton were investigated as organocata-lysts for asymmetric aldol reactions between nitromethane and p-nitrobenzaldehyde in the presence of CuCl. Enantiomeric excesses and the reaction yields were found to be appropriate values. Furthermore, the best or-ganocatalyst applied in this study was identified after careful optimization of conditions. Lastly, all of the novel compounds were subjected to computational analysis at the B3LYP/6-31++G(d, p) level of theory to obtain in-formation about their structural and electronic properties. © 2020, Macedonian Journal of Chemistry and Chemical Engineering.
2-s2.0-85086514292
Keywords: Asymmetric catalyst; Chiral amino alcohol; Chirality; Lewis acid; Pyrazole